2014
DOI: 10.1111/ics.12181
|View full text |Cite
|
Sign up to set email alerts
|

Chemical analysis and risk assessment of prohibited colouring agents in face paint with special regard to CI 15585 (D&C Red No. 9, Pigment Red 53:1)

Abstract: An analytical strategy to determine colouring agents in face paints was developed and non-compliance with the European Union (EU) cosmetic products regulation in a considerable number of products was detected. An increased control frequency especially at the points of entry into the EU is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Standard face paint products for professionals are subjected to frequent random market controls in Western countries, in accordance with European Union (EU) cosmetic product regulations [36]. However, face paint, which is often used by Chinese traditional opera (Xiqu) performers, tends to be unregulated in China [51].…”
Section: Xiqu Performers Suffer From Skin Problemsmentioning
confidence: 99%
“…Standard face paint products for professionals are subjected to frequent random market controls in Western countries, in accordance with European Union (EU) cosmetic product regulations [36]. However, face paint, which is often used by Chinese traditional opera (Xiqu) performers, tends to be unregulated in China [51].…”
Section: Xiqu Performers Suffer From Skin Problemsmentioning
confidence: 99%
“…The development of spleen sarcoma was reported in a long‐term NTP feeding study of male rats in which, because the genotoxicity test was negative, the carcinogenic effect was assessed by threshold with NOEL 25 mg/kg bw. The study authors found that the carcinogenic potential expressed as TD50 (the dose that induces tumors on half of test animals) was 104 mg/kg bw/day 8 . On October 4, 2022, in Public Warning No.…”
Section: Introductionmentioning
confidence: 98%
“…The study authors found that the carcinogenic potential expressed as TD50 (the dose that induces tumors on half of test animals) was 104 mg/kg bw/day. 8 On October 4, 2022, in Public Warning No. PW.02.04.…”
mentioning
confidence: 99%
See 2 more Smart Citations